Wpływ standardów kształcenia na poziom nauczania matematyki w wyższych szkołach ekonomicznych - Maciuk, Arkadiusz (The influence of education standards on the level of mathematics teaching in economic universities, 2011)
The education standards introduced in Poland in 2005 by the new higher education law significantly changed rules of teaching of majority of subject taught at universities. From the perspective of teaching mathematics at universities of economics those standards have several serious drawbacks such as reduction of the number at maths teaching hours without significant modifications of curriculum or bad correlation with what is being taught in high schools. The law of 2005 was supposed to improve the effectiveness of teaching and make students better prepared for challenges of the work market. Teaching of mathematics at the universities of economics should, apart from providing necessary tools for further study, help students become independent and develop abilities of analytical thinking. Unfortunately, practice is different and to a very large extent this is due to the present standards. Few years after they were introduced we are trying to indicate what actions should be taken to improve the quality of mathematics teaching and in consequence facilitate students’ independent conclusions and enhance their analytical thinking skills
Didactics of Mathematics, 2011, Nr 8 (12), s. 81-90
Keywords: education standards; mathematics teaching